Human physiology - Fox, Stuart Ira (Wm. C. Brown Publishers, 1993)
Tissues, organs, and control systems.--Chemical composition of the body.--Cell structure and genetic control.--Enzimes and energy.--Cell respiration and metabolism.--Membrane transport and the membrane potential.--The nervous system.--The central nervous system.--Sensory physiology.--The autonomic nervous system.--Endocrine glands.--Muscle.--Haeart and circulation.--Cardiac output, blood flow, and blood pressure.--Respiratory physiology.--Physiology of the kidneys.--The digestive system.--Regulation of metabolism.--The immune system.--Reproduction.